2020
DOI: 10.1002/btpr.2965
|View full text |Cite
|
Sign up to set email alerts
|

Response‐surface methodology for the production and the purification of a new H2O2‐tolerant alkaline protease from Bacillus invictae AH1 strain

Abstract: This work deals with the optimization of the culture conditions of Bacillus invictae AH1 in order to increase the production level of the proteolytic activity. Response‐surface methodology (RSM) was applied for the most significant fermentation parameters (concentration of wheat bran and K2HPO4/KH2PO4) that were earlier identified by Plackett–Burman Design from seven possible factors. A central composite design was used and the quadratic regression model of producing active protease was built. A maximum protea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 66 publications
2
8
1
Order By: Relevance
“…Moreover, in comparison to previous reports suggesting proteases from Bacilli had low K m between 0.57 and 4.0 mg/ml at higher temperatures (45–60 °C) 41 , 55 57 , the Apr-BO1 had a low K m (1.0 mg/ml) and V max (10.0 µmol/ml/min) at low temperature (20°), which indicates that it has high substrate affinity and efficient catalytic activity. The sequence of Apr-BO1 and other similar proteases showed low similarity after comparing with the database available at UniProt ( https://www.uniprot.org/blast/ ).…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Moreover, in comparison to previous reports suggesting proteases from Bacilli had low K m between 0.57 and 4.0 mg/ml at higher temperatures (45–60 °C) 41 , 55 57 , the Apr-BO1 had a low K m (1.0 mg/ml) and V max (10.0 µmol/ml/min) at low temperature (20°), which indicates that it has high substrate affinity and efficient catalytic activity. The sequence of Apr-BO1 and other similar proteases showed low similarity after comparing with the database available at UniProt ( https://www.uniprot.org/blast/ ).…”
Section: Discussioncontrasting
confidence: 70%
“…Inhibition observed in Apr-BO1 enzyme for the present study was not as sturdy as reported for various serine alkaline proteases from Bacillus pumilus AI 38 , Bacillus sp. ZJ1502 39 , Bacillus safensis S406 40 and Bacillus invictae AHI 41 , adds to its novelty.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table 1, the presence of PMSF, which is the inhibitor of serine peptidases, caused a decrease in the peptidase activity. It was determined that serine peptidases are generally stable at pH 8.0 (Mothe & Sultanpuram 2016, Hammami et al 2020). It was observed that the stability of the enzyme decreased in alkaline conditions, especially for more extended incubation periods (Fig.…”
Section: Optimum Ph Of Peptidase and Ph Stabilitymentioning
confidence: 99%
“…The enzyme used in the detergent had to be stable in a wide range of temperature and had to be active in the presence of various surfactants, bleaching agents, and various other additives. Currently, a large proportion of commercially available protease is derived from Bacillus strains and most of them were isolated from coastal regions [7][8][9][10][11]. From the study of the previous literature, it can be seen that due to the longest coastal region of Gujarat the possibility of getting the isolate with very good alkaline protease production is high [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…carbon source, nitrogen source, etc.) and therefore optimization of the factors is essential to improve the protease yield [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. A number of statistical experimental designs with response surface methodology (RSM) have been employed for optimizing enzyme production from microorganisms [21].…”
Section: Introductionmentioning
confidence: 99%